OHP-074 the Chronic Obstructive Pulmonary Disease in Azienda Sanitaria Provinciale Siracusa: Economic Considerations Related Appropriateness of Prescription. (12th March 2013) - Avola, N; Guzzardi, S; Sgarlata, D; Sorbello, R; Cacciaguerra, G; Scandurra, A
Abstract : Background: In Italy respiratory diseases are the third cause of death, 50% of which is caused by Chronic Obstructive Pulmonary Disease (COPD). COPD is an irreversible inflammation that causes narrowing of the airways and has a slow and progressive course. In Siracusa the high incidence of COPD may be due to the petrochemical plants in the area. Drug treatment allows us to improve quality of life and to reduce mortality, but often the prescriptions do not adhere to the GOLD Guidelines (GL) for COPD treatment. Purpose: To assess the budgetary impact of the treatment used and of the GOLD GL treatment. Materials and Methods: The authors obtained, by administrative databases and mathematical models: The prescriptions of medicines for COPD (ATC R03) in 2010 in Azienda Sanitaria Provinciale (ASP) Siracusa; The number of patients with COPD; The number of patients for each stage of severity; The budget impact of the treatment used and the GOLD GL treatment, which recommends: using SAMAs/SABAs(short-action antimuscarinics/antiadrenergics) in the mild stage; adding LAMAs/LABAs(long-action antimuscarinics/antiadrenergics) from the moderate to very severe stage; to add FDCs (fixed combination drugs)/ICSs (inhaled corticosteroids) in severe and very severe stages. Results: 5895 patients had COPD, of whom: 1484 in mild stage; 2672 in moderate stage; 1155 in severe stage; 584 in very severe stage. The spending for drugs prescribed for COPD was €2, 702, 627 of which €1, 787, 967 was for FDCs/ICSs. If the prescriptions were 100% adherent to GOLD GL spending would have been €1, 309, 304, of which €434, 029 for FDCs/ICSs, with a saving of €1, 393, 323. Conclusions: If the prescriptions of FDCs/ICSs adhered to GOLD GL, spending would have been 50% less. The adherence to GOLD GL ensures the patient a proper prescription and allows high savings. The authors are developing a training-information project aimed at encouraging doctors to prescribe appropriately. No conflict of interest.